DNA extraction efficiency from soil as affected by pyrolysis temperature and extractable organic carbon of high-ash biochar. (December 2017) - Dai, Zhongmin; Webster, Tara M.; Enders, Akio; Hanley, Kelly L.; Xu, Jianming; Thies, Janice E.; Lehmann, Johannes
Abstract: Biochar additions to soil have, in some cases, been shown to reduce the DNA extraction efficiency, but the mechanisms remain unclear and commonly used high-ash biochars have not been investigated. We studied the effects of pyrolysis temperatures (300 or 700 °C), post-pyrolysis extractable organic carbon (separating acetone extractable C, AeC), and soil incubation on DNA extraction efficiency using high-ash swine manure biochar. We used quantitative PCR to measure the extraction efficiency of an internal DNA standard ( Aliivibrio fischeri ) added to samples before extraction. DNA extraction efficiency from biochars decreased by 39% as pyrolysis temperature increased from 300 to 700 °C (p < 0.05). AeC from biochar 300 °C increased DNA extraction efficiency for biochars made at both pyrolysis temperatures and when added to biochar 700 °C, the extraction efficiency increased by 52% (p < 0.05). Incubation in soil increased DNA extraction efficiency from isolated biochar particles by up to 28% (main effect p < 0.05). However, biochar-soil mixtures had up to 24% lower DNA extraction efficiency compared to what would be predicted based on a simple mixing model of incubated soil and separated biochars. Biochar pyrolysis temperature, extractable C, and incubation with soil were all associated with changes in DNA extraction efficiency. The differences in DNA extraction efficiency indicated that caution must be exercised when comparing microbial abundance and diversity with different biochar additions, even for high-ash biochars. Graphical abstract: Highlights: High-ash biochars can reduce DNA extraction efficiency from soil. Hydrophobic interactions may cause low extraction efficiencies with biochar. DNA extraction efficiencies from biochar particles increase over time. Biochar decreases extraction efficiency of surrounding soil over time.